Impact of mycorrhizal colonisation on grapevine establishment in Cylindrocarpon infested soil - Bleach, C.M.; Cope, R.J.; Jones, E.E.; Ridgway, H.J.; Jaspers, M.V. (New Zealand Plant Protection, 2008)
The effects of arbuscular mycorrhizae (AM) Glomus mosseae and Acaulospora laevis on growth of six grape rootstock varieties and their infection by Cylindrocarpon species were investigated in a greenhouse experiment that challenged the mycorrhizal plants with a mixed inoculum of Cylindrocarpon spp Both species of AM had beneficial effects (P005) but greater root dry weights in Auckland (214; P005) G mosseae clearly has potential for improving health and growth of young grapevine plants